Actualities of formation of the sovereign fund of well-being of Ukraine in the post-war period - Karapetian, Olha (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
The peculiarities of forming a single sovereign fund of Ukraine with a vector for stabilization and postwar development are considered, which made it possible to establish how these funds can be used in the project of international financial assistance and development of world policy coherence around fiscal ideologies of international financial organizations.The article defines the essence of sovereign wealth funds and forms the main stages of their development, outlines the main classification features inherent in sovereign wealth funds. The theoretical foundations of the functioning of sovereign wealth funds are analyzed.It is determined that one of the most effective tools used to increase public welfare through the use of state resources, which according to the Constitution belong to the whole people, are sovereign welfare funds.It is established that sovereign wealth funds are an essential source of financing for the development of the world economy and, at the same time, a tool for increasing the influence of state capital of individual countries on the global economy.They are not formed from tax revenues from goods sold on the domestic market. The main task is to increase welfare, not redistribution of budget funds.The article considers the sources of filling the sovereign wealth fund, offers new ways to ensure financial stabilization through the use of financial reserves accumulated in sovereign wealth funds.The management system of this fund should include cross-checking and transparency of project competitions. Therefore, the activities of the fund will be monitored by an expert and supervisory board.It is argued that the formation of a sovereign welfare fund in the postwar period acts as an infrastructural holistic support for the formation of a new type of civic responsibility for the common good, fostering a sense of common historical destiny.